What explains trends in Australian working-time arrangements in the 2000s?. (2nd April 2016) - Venn, Danielle; Carey, Gemma; Strazdins, Lyndall; Burgess, John
ABSTRACT: The 1980s and 1990s witnessed a deterioration in working-time arrangements for employees in Australia, driven by globalisation, demographic and structural change and labour market deregulation. Yet, working-time arrangements in the first decade of the 2000s have either improved for employees or stayed relatively unchanged despite continued global pressures and further reforms of domestic labour law. Fewer employees are working long hours or at antisocial times, hours variability has fallen and employee control over working time has increased. This paper attempts to explain the apparent levelling out of previous downward working time trends using data from the Household Income and Labour Dynamics in Australia (HILDA) Survey. Decomposition analysis shows that the improvement in working-time arrangements can be partly attributed to an increase in the skill level and earnings potential of the workforce and a general improvement in economic conditions. We show that the Fair Work industrial relations reforms of 2009 may have also contributed to the overall improvement in working-time arrangements, but this was partially offset by the negative effects of the global financial crisis.